Design and Implementation of Non-Contact Infrared Thermometer based MLX90614 and Ultrasonic Sensors - Inayatul Inayah; Heri Kiswanto; Achmad Dimyati; Muhammad Ghofinda Prasetia (Jurnal Fisika dan Aplikasinya, 2022)
Masurement of body temperature is essential to know the condition of the individual’s body. Temperature measurements need to be carried out without contact between individuals and devices or individuals with other individuals to prevent the transmission of Covid-19. In this study, a non-contact thermometer has been designed using an MLX90614 sensor to measure body temperature, and an HC-SR04 ultrasonic sensor to detect objects at 5-30 cm. The sensor reading results will be displayed via the TFT LCD in real-time. If the detected object temperature exceeds 37.5 oC, the buzzer will sound, and the LED will light up. The constructed thermometer is supplied by 12 V DC adapter to provide 5 V output to the microcontroller. Proximity sensor, temperature sensor, and TFT LCD work on 5 V DC voltage. A Resistor and a transistor were needed to turn on the LED and 12 V high decibel buzzer. This instrument has been tested and compared with a commercial thermometer AD801 model for measuring palms and forehead. Based on our study, the difference in palm and forehead temperature readings between the two thermometers in two individuals ranges from 0 to 0.2 oC. This reading error was still within the tolerance of the reading error listed on the MLX90614 sensor datasheet, which is ± 0.3 oC.